EGG LAYING PERFORMANCE OF CHICKENS FED GRADED LEVELS OF DISCARDED UNDEFATTED CASHEW KERNEL (DUCK) MEAL - Alhassan, M.; Mintaah, A. N. (UDS International Journal of Development, 2018)
A 12-week study was carried out to determine the effect of dietary levels of discarded undefatted cashew kernel (DUCK) meal on feed digestibility and egg laying performance of layer chickens. The cashew kernel was toasted for about 10 minutes in hot iron pot. After toasting, it was allowed to cool and then milled into gritty floor, bagged and labelled DUCK meal. The DUCK meal was incorporated in layer concentrate-based diets at 4 levels (0, 50, 75 and 100 g/kg). In the digestibility trial, 12hens were randomly assigned to the 4 dietary treatments with 3 replicates per treatment. Known quantities of the experimental diets were weighed and supplied to the hens daily for 5 days. The faeces were collected in plastic sheet placed under the wire-mesh floor of the cages using the Total Collection Method. Samples of the experimental diets and faeces were subjected to proximate analysis and subsequently used for computing the nutrient digestibility.At 29 weeks of age, 120 ISA Brown layers were divided into 4 groups with 3 replicates per group comprising 10 hens per replicate in a Completely Randomized Design during the feeding trial. Feed and water were given ad libitum from 30 to 41 weeks of age. Data collected on nutrient digestibility, egg production and physical egg characteristics were subjected to ANOVA in GenStat. Dry matter digestibility reduced (P<0.05) in birds fed 10% DUCK meal. Whilst protein digestibility was not affected (P>0.05), fat and ash digestibility improved with increasing levels of DUCK meal in the diet. There was no significant (P>0.05) difference in all egg production parameters measured except for hen-day egg production. Birds fed diets containing 0 and 50 g/kg DUCK meal were similar (P>0.05) but higher (P<0.05) than those birds fed 75 g/kg DUCK meal for hen-day egg production. Those birds fed 100 g/kg DUCK meal had the lowest (P<0.05) egg production performance. Physical egg characteristics did not differ (P>0.05) among treatment groups. The study concluded that DUCK meal in diets of laying chickens had no adverse effects on protein digestibility, improved fat and ash digestibility and had adverse effect on egg production beyond 50 g/kg dietary inclusion. Keywords: cashew kernel, egg production, toasting, undefatted